Avaliação da composição química e tratamentos térmicos da carne ovina de animais submetidos à dieta com o subproduto do urucum (Bixa orellana L.) - FERREIRA, Eldânia Soares (2015)
The meat products are subject to oxidative processes that promote the appearance of compounds harmful to consumer health such as cholesterol oxides and malondialdehyde, which are closely related to the onset of cardiovascular diseases and cancers, and are responsible for the deterioration of product. To minimize these processes the industry has used synthetic antioxidants such as butylhydroxytoluene, butylhydroxyanisole, BHT and BHA, however, these compounds have the disadvantage of being related to the promotion of cancer, in special lung. So the industry is looking for alternatives that provides protection to products without causing harm to human health, and carotenoids stand out because they are natural antioxidants that can guarantee protection to the product, in addition to enabling activities beneficial to health, especially protection from the action of free radicals, which participate in the startup process and development of various diseases. This study aimed to evaluate the thermal stability of the sheep meat fed the byproduct of annatto subjected to different thermal treatments. The experimental design was completely randomized in a 4x4 factorial scheme (four thermal treatments and four bixin concentrations in the flesh).The thermal treatments were: fresh, cooking, oven and frying, and were used for inclusion levels of the byproduct of annatto the diets provided the following concentrations of bixin: (1) no addition, (2) with addition of 0.056 mg (3) mg and 0.113 (4) 0.169 mg of bixin / kg of feed (dry matter basis). Samples were obtained from the cross section of the named commercial cut tenderloin. To determine the chemical and thermal stability, the following analyzes were performed: dry matter, crude protein, ether extract, thiobarbituric acid reactive substances (TBARS), cholesterol and cholesterol oxides (COPs) in the meat. The heat treatment caused changes in the chemical composition of meat and the formation of reactive substances barbiturate acid (TBARS) (P <0.05). The bixin gave oxidative stability of fresh beef (P <0.05), indicating the effectiveness of its use in increasing life. However, the carotenoid was not effective to inhibit oxidation during heat treatments (P> 0.05). The concentration of COPs was high by heat treatment (P <0.05). The contents of 0.109 and 0.164 mg of bixin inhibit the formation of COPs (P <0.05). It is concluded that bixin does not alter the chemical composition of the lamb meat, and that heat treatments contribute to elevation of the meat constituents. The bixin was able to slow down the oxidative processes of sheep meat in natura. But does not give the same effect on handling meat. The heat treatments in combination with bixin promoted reduction of cholesterol in meat.